Social-Philosophical Analysis of Innovation Culture Formation Problems - Mirzoyan, Valeri (Bulletin of Yerevan University E: Philosophy, Psychology, 2021)
In this article, some problems of innovation management in the frame of social-philosophical generalization are discussed. According to author, cultural factors are as important for effective innovation process as economical, technological and organizational factors. Both on organizational and societal levels, there must be an adequate cultural climate, which motivates people to desire to seek out new creative ideas, new ways to improve products and technologies, new methods for business and for organization of social life.